A General Framework for Knowledge Management in an Educational Institution - Pai, Srinivasa; Pai, Asha S. (Journal of Engineering Education Transformations, 2005)
Knowledge Management (KM) has been a buzzword in the business circles and the amount of literature available on this subject, highlights its emergence as a new paradigm in the business world. This new era of the "knowledge based economy", one which values the enhancement of work efforts through the use of knowledge and increased productivity and innovation, has the power to completely transform not only the foundations of business, but also, according to Peter Drucker; to profoundly change the very fabric of society [I]. This statement emphasizes the importance of knowledge and how it is going to affect every facet of life. Education being the core activity, upon which the social well being of a nation depends, is a knowledge intensive activity. The use of KM as a means for effectively managing education in an educational Institution is the theme of this paper. Efforts are on around the world to use KM for effectively managing the education delivery process. This paper tries to present a broad and general overview of KM and how it can be applied to education. A general framework for KM in an educational institution is presented, which can help an institution in its efforts and really yield the benefits.